Antioxidant Function and Application of Plant-Derived Peptides - Zhengqing Zhu; Ziwu Xu; Yuhang Li; Yutong Fan; Yingqian Zhou; Kaixin Song; Lei Meng (MDPI AG, 2024)
With the development of society and the improvement of people's health consciousness, the demand for antioxidants is increasing. As a natural antioxidant with no toxic side effects, antioxidant peptides are widely used in food, cosmetics, medicine, and other fields because of their strong antioxidant capacity and easy absorption by the human body. Plant-derived antioxidant peptides have attracted more attention than animal-derived antioxidant peptides because plants are more diverse than animals and produce a large number of protein-rich by-products during the processing of their products, which are the main source of antioxidant peptides. In this review, we summarize the source, structure and activity, other biological functions, mechanism of action, and comprehensive applications of plant antioxidant peptides, and look forward to their future development trends, which will provide a reference for further research and development of plant antioxidant peptides.